マラジョージナヤ キチ ト ミルニー キチ デ エタ ケイソウ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1966)
P(論文) The author investigated the diatoms in inland waters around Molodezhnaya Station and Mirny Station. Seven materials from the former station were collected by the 7th Japanese Antarctic Research Expedition on February 4, 1966, and five materials from the latter station were collected by Dr T MATSUDA, Department of Polar Research, National Science Museum, in February 1965. Seven taxa of diatoms were found from two lakes around Molodezhnaya Station, and five of them could be identified. Of these five diatoms, Fragilanopsis antarctica and F. obhquecostata are Antarctic Ocean endemic species, and Navicula muticopsis is antarctic endemic species. From this fact, we can say that inland water diatoms around Molodezhnaya Station have a stronger cosmopolitan factor than an Antarctic factor. Ten taxa of diatoms were found in the five materials from around Mirny Station. Of them, Fragilanopsis curta, F. obhquecostata and F rhombica are Antarctic Ocean endemic species, and Navicula muticopsis v. muticopsis f muhcopsis and N. m v m f. munayi are Antarctic inland water endemic species. N. muticopsis v. muticopsis f. muticopsis, mentioned above, was dominant in two of the five materials, and Pinnulana boreahs which is a cosmopolitan species, was dominant in one material This fact suggests that the inland water diatom flora around Mirny Station has a strong Antarctic endemic factor as well as a strong cosmopolitan factor. departmental bulletin paper